The Role Of Green Economy In Ncouragig Enterpreneurial Innovation Of MSME Coconut Ice Sellers - Cailah Nasywa Afrila; Diah Indri Anggriyanti; Dela Wahyu Putri Awanda; Maria Yovita R. Pandin (Kajian Ekonomi dan Akuntansi Terapan, 2024)
The purpose of this study on the Role of Green Economy in Encouraging Entrepreneurial Innovation of MSME’s Selling Coconut Ice is to find out how to classify waste that can be processed into something that can be reused and waste that cannot be processed. Coconut ice sellers sometimes do not know how coconut waste can be processed into something that has economic value. Therefore, coconut ice sellers only sell coconut to be made into coconut ice with various variants by providing innovative flavors other than original such as palm sugar flavors, or using flavored syrups. With so many coconut ice sellers today, there is a large amount of coconut waste generated every day. Materials that sometimes cause waste in MSME entrepreneurs selling coconut ice are waste that is not used or discarded such as coconut shells, coconut fibers, syrup bottles, milk cans, and plastic (other waste). This is a problem for traders who have difficulty distributing waste so that it can be processed into something that can be used or useful and has economic value for waste that is reprocessed. To emphasize the environmentally friendly aspects of coconut waste and can increase the attractiveness for consumers to care about their environment regarding the waste. So from the conclusion of this research can emphasize, how important the green economy is in encouraging innovation regarding entrepreneurship in MSME’s for coconut ice sellers.